دراسة تحليلية لمراقبة التسيير و علاقتها باتخاد القرار - بن علي, إيمان (My University, 2020)
The analytical study of management control represents one of the basic tasks performed by the management controller within the economic institution on which the success of the management process depends, especially in light of the current environment characterized by globalization, rapid exchange, technological level development and intense competition, due to the characteristics and tools that enable the management to Measuring and evaluating the performance of the institution and taking the appropriate decision aimed at achieving its objectives, just as small and medium enterprises, which have become occupying a large place in the economic process for developed or developing countries alike, need to use modern monitoring tools in order to withstand and continue in front of the challenges they face As is the case with the Algerian economic institutions, they need more because of the transformations in the economic environment in Algeria, and to achieve this, consideration must be given to the good choice of a qualified management controller for the success of the work of the economic institution because he is primarily responsible for its sustainability and prosperity. Away from the deviations and mistakes, and because he is the one who conducts studies and analyzes before and after the occurrence of problems to avoid them or to solve them radically by taking and making sound decisions based on modern tools for monitoring management and assisting in decision-making. To carry out his powers to have us put "the right man in the right place".